Analytical Solution of Fractional Oldroyd-B Fluid via Fluctuating Duct. (22nd November 2021) - Song, Ying Qing; Farooq, Aamir; Kamran, Muhammad; Rehman, Sadique; Tamoor, Muhammad; Khan, Rewayat; Fahad, Asfand; Qureshi, Muhammad Imran
Abstract : This investigation focuses on the mixed initial boundary value problem with Caputo fractional derivatives. The studied pour an incompressible fractionalized Oldroyd-B fluid prompted by fluctuating rectangular tube. The explicit expression of the velocity field and shear stresses for the fractional model are obtained by utilizing the integral transforms, i.e., double finite Fourier sine transform and Laplace transform. Furthermore, the confirmation of the analytical solutions is also analyzed by utilizing the Tzou's and Stehfest's algorithms in the tabular form. In limited cases, ordinary Oldroyd-B fluid similar solutions and classical Maxwell and fractional Maxwell fluid are derived. The flow field's graphs with the influences of relevant parameters are also mentioned.